2017
DOI: 10.1111/jcmm.13432
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of mitochondrial complex I improves glucose metabolism independently of AMPK activation

Abstract: Accumulating evidences showed metformin and berberine, well‐known glucose‐lowering agents, were able to inhibit mitochondrial electron transport chain at complex I. In this study, we aimed to explore the antihyperglycaemic effect of complex I inhibition. Rotenone, amobarbital and gene silence of NDUFA13 were used to inhibit complex I. Intraperitoneal glucose tolerance test and insulin tolerance test were performed in db/db mice. Lactate release and glucose consumption were measured to investigate glucose metab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
78
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(88 citation statements)
references
References 32 publications
(44 reference statements)
8
78
0
2
Order By: Relevance
“…In L6 muscle cells, the ability of PF to enhance glucose uptake was partially reversed by stable NDI1 expression, indicating that the decrease of mitochondrial complex 1 activity contributes to the stimulatory effect of the compound on muscle glucose uptake. This conclusion is also supported by previous studies showing that inhibition of mitochondrial complex 1 by a very low dose of rotenone or siRNA-mediated silencing of NADH:Ubiquinone Oxidoreductase Subunit A13, a subunit of complex I, can reduce hepatic glucose production and stimulate glucose consumption in muscle cells, independently of AMPK (28). In addition, other studies have reported similar mechanisms.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…In L6 muscle cells, the ability of PF to enhance glucose uptake was partially reversed by stable NDI1 expression, indicating that the decrease of mitochondrial complex 1 activity contributes to the stimulatory effect of the compound on muscle glucose uptake. This conclusion is also supported by previous studies showing that inhibition of mitochondrial complex 1 by a very low dose of rotenone or siRNA-mediated silencing of NADH:Ubiquinone Oxidoreductase Subunit A13, a subunit of complex I, can reduce hepatic glucose production and stimulate glucose consumption in muscle cells, independently of AMPK (28). In addition, other studies have reported similar mechanisms.…”
Section: Discussionsupporting
confidence: 84%
“…(NADH:ubiquinone oxidoreductase) plasmid was a gift from David Sabatini (Addgene plasmid #72876) and the pMXS-control vector was kindly provided by Kivanc Birsoy (Rockefeller University, USA). Plasmids were amplified as previously described in Phoenix-Eco cells (ATCC #CRL-3214) (28). Undifferentiated rat L6 myoblasts were infected with the amplified retrovirus and selected with 5 µg/ml of blasticidin to generate L6-pMXS and L6-NDI1 stably transfected myoblasts.…”
Section: Ndi1 Expression In L6 Cells the Pmxs-ndi1mentioning
confidence: 99%
“…Interestingly, both IACS/VIN and RT/2-DG combinations significantly enhanced ECAR (extracellular acidification rate) by 27-234% in MOLM-13 cells and studied patient samples (n = 5/6), as well as in PBMCs in case of IACS/VIN (Table S8). Previous reports have shown that inhibiting Complex I of the ETC with IACS-010759 or rotenone upregulates glucose consumption and glycolysis (42,43). As expected, normalized coupling efficiency was also significantly associated (r = 0.786, p < 0.001) with ATP-linked OCR ( Figure 7E).…”
Section: Iacs-010759/vinorelbine and Rotenone/2-deoxy-d-glucose Combisupporting
confidence: 82%
“…Cell viability was measured using the cell counting kit -CCK8 assay Kit(Dojindo, Japan)(n = 6/group). The percentage of living cells was calculated as previously described in a study [16].…”
Section: Cell Viability Assay By Cck8mentioning
confidence: 99%